When Does Private Discrimination Justify Public Affirmative Action - Ayres, Ian (SSRN eLibrary, 1998)
At a moment when judicial tolerance of race-conscious government action seems to be waning, this Article develops a new set of constitutionally viable justifications for affirmative action. Rather than enter the familiar debate over the legitimacy of the Court's application of strict scrutiny to remedial affirmative action, Ayres & Vars excavate widely overlooked language in the Supreme Court decision in City of Richmond v. J.A. Croson Co., which notes the ability of government to eradicate the effects of private, not just governmental or public, discrimination. The authors develop three justifications for remedying private discrimination through public affirmative action, each of which produces non-arbitrary goals that do not unduly burden innocent third parties—making them narrowly tailored to a compelling governmental interest. Thus, the authors re-cast Croson, an opinion routinely understood as the death knell for affirmative action, into a model for its redirection and possible expansion. Beginning with the story of Marian Anderson's 1939 concert at the Lincoln Memorial the authors demonstrate how public affirmative action used to remedy private discrimination is neither counter-intuitive nor unprecedented in our historical memory. They then focus on affirmative action in government procurement, and demonstrate how the larger size of private markets and the stronger evidence of private discrimination suggest that the future of affirmative action in procurement may turn largely on private discrimination justifications. Three private discrimination rationales follow: (1) to ensure that government spending does not directly or indirectly facilitate private discrimination (the causal justification); (2) to correct for the depressive effect of private discrimination on the capacity of minority-owned firms (the but-for justification); and, most radically, (3) to compensate for shortfalls in private sales caused by purely private discrimination, so long as the scope of the government remedy is restricted to that particular market (the single-market justification). The Article applies the justifications it offers to the related context of employment and argues that public remedies for private discrimination in employment can be narrowly tailored. Thus, a position which at first appears to be incompatible with the Supreme Court's present unwillingness to uphold affirmative action programs emerges as a remarkably compelling and constitutionally grounded argument in support of the government's ability to remedy private discrimination in a wide array of settings